In War and in Peace (Sello Editorial Ejército Nacional de Colombia, 2024)
This book by Eduardo Pizarro serves to fill a gap. It first points out one of the reasons: the profound ignorance and laziness of civilians in analyzing security issues; with honorable, but very few exceptions —Francisco Leal, Armando Borrero, Alejo Vargas, Andrés Dávila, María Victoria Llorente...—, politicians, journalists, and academics have hardly begun to do the work. The country has produced many specialists in violence, but few have shown interest in the Army. The author finds a root of this laziness in the speech of Alberto Lleras Camargo at the Teatro Patria on May 9, 1958, after the failed coup attempt of May 2 of the previous year. I have reread this exceptional piece very carefully. Lleras spoke of two distinct spheres: the civil and the military, and of the need for each to recognize the prerogatives of the other. I must point out that I find the interpretation that has been made of this speech inadequate; it has been criticized for not having recognized the responsibility that military personnel have to understand that their matters inevitably have political dimensions, nor the responsibility -the ultimate responsibility in a democracy is theirs, the civilians’, not the uniformed’s- that civilians have to participate in the intelligent design of military institutions and the strategies they must formulate. Pizarro briefly summarizes certain key moments in the evolution of the Military Forces: the beginnings of professionalization with the Chilean Mission, requested by President Rafael Reyes, which marked the beginning of the end of the old party armies; the war with Peru, which although brief and distant, demanded an enormous effort that unfortunately left no useful lessons for addressing violence problems after 1946; participation in the Korean War and the counterinsurgency reorientation of the early 1960s, with the emergence within the officer corps of certain developmentalist thought currents, whose leading exponents were General Alberto Ruiz Novoa and, until his death, General Álvaro Valencia Tovar, an educator of civilians of admirable persistence.